Dialysate and plasma meropenem concentrations in continuous intraperitoneal regimen during peritoneal-dialysis-related peritonitis - Thatsaphan Srithongkul; Sukit Raksasuk; Bulaporn Techajongnumchai; Suchai Sritippayawan; Pornpan Koomanachai (PLoS ONE, 2025)
Background A single dose of intraperitoneal (IP) meropenem is recommended for peritoneal-dialysis (PD)-related peritonitis stemming from extended-spectrum β-lactamase-producing organisms. However, data on IP meropenem is limited. Methods This prospective, descriptive study was conducted to examine plasma and dialysate meropenem levels during continuous IP meropenem administration in five patients with PD-related peritonitis. All patients received an IP meropenem loading dose of 500 mg, followed by IP meropenem at 125 mg/L, with four exchanges daily. The plasma and dialysate meropenem concentrations were measured at specified intervals for a 24-hour period utilizing a high-performance, liquid chromatography method. Results Five patients with PD related peritonitis were studied. The mean-maximum dialysate and plasma meropenem levels were 158.1 mg/L (standard deviation [SD] ± 62.9) and 29.4 mg/L (SD ± 15.9), respectively. The mean dialysate meropenem level was at its minimum of 32.6 mg/L (SD ± 19.1) at 24 hours. Throughout the period, the dialysate meropenem levels exceeded the minimal inhibitory concentration of the pathogenic resistance organism (> 8 mg/L). Four patients responded to the treatment, whereas one developed treatment failure from fungal peritonitis. Conclusion An IP meropenem loading of 500 mg, followed by 125 mg/L every 6 hours, provided an adequate dialysate meropenem concentration and is an effective treatment for PD related peritonitis. Trial registration Thai Clinical Trials Registry (TCTR20191121002) with date of first registration at 21/11/2019 (retrospectively registered).